Governance Principles Driving Sustainable Village Economic and Social Development - Mochammad Rossy Dukhan Muhith; Agus Widiyarta (Academia Open, 2025)
General Background: Village-Owned Enterprises (BUMDes) serve as key instruments for advancing local economic development and community welfare within Indonesia’s rural governance system. Specific Background: Despite their strategic role, many BUMDes—including BUMDes Raharja in Bohar Village—struggle to fully implement good governance principles due to challenges in financial independence, human resource capacity, and digital transparency. Knowledge Gap: Previous studies have emphasized the economic contributions of BUMDes but have insufficiently explored the integrated application of cooperative, participatory, emancipatory, transparent, accountable, and sustainable governance principles in shaping inclusive and resilient village economies. Aims: This study analyzes the implementation of good governance principles in BUMDes Raharja and evaluates their effects on community welfare and institutional sustainability. Results: Findings reveal that while BUMDes Raharja successfully fosters cooperation, participation, and transparency, limitations persist in financial autonomy, digital management, and inclusivity. Novelty: The study integrates six governance dimensions within a unified analytical framework, offering a comprehensive perspective on governance-driven rural empowerment. Implications: Strengthening human resources, promoting digital transformation, and establishing inclusive policies are crucial for enhancing accountability, participation, and long-term sustainability in village economic governance. Highlights: Highlights the integration of six governance principles in BUMDes management. Identifies key challenges in financial independence and digital transparency. Emphasizes inclusive, participatory governance for sustainable rural empowerment. Keywords: Village-Owned Enterprises, Good Governance, Community Welfare, Rural Development, Transparency